Methodologies for Estimating Bioaccessibility of Six Metals in Household Dust: Zn, Pb, Cd, Cu, Ni, and Cr - Boros, Kristina (Université d'Ottawa / University of Ottawa, 2015)
The purpose of this study is to evaluate the relative advantages and disadvantages of two approaches for estimating oral bioaccessibility using a physiologically-based extraction technique (PBET): a simple gastric phase simulation and a two-phase gastrointestinal simulation. Bioaccessibility estimates of six metals prevalent in Canadian contaminated sites (zinc, lead, cadmium, copper, nickel, and chromium) were compared using the gastric phase simulation alone and the complete gastrointestinal simulation. Samples included vacuum dust samples from 33 homes, certified dust and soil reference materials, and a house dust control sample. Bioaccessibility measurements using the gastric phase simulation were greater than or equal to measurements obtained using the gastrointestinal simulation for the six studied metals. This research found that for the six studied metals, a simple simulation of the gastric phase provides the most conservative and cost-effective approach for estimating oral bioaccessibility of ingested metals.
Keywords: Household dust; Dust; Soil; NIST; Bioaccessibility; Trace Metals